PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 2 LUBUK ALUNG - Mardhiah, Ainil (Departemen Matematika, 2023)
Understanding maths is essential for students. However, at SMPN 2 Lubuk Alung, this capability is still s ubpar. The teacher-centered, educator-dominated nature of the learning process is one of the root reasons of this issue. Other mathematical skills will suffer if this one is weak. In class VIII SMPN 2 Lubuk Alung during the 2023–2024 academic year, the study's objectives were to analyze the increase in concept understanding of students who learn with the Contextual Teaching and Learning (approach and describe whether or not the concept understanding of students who learn with this approach is superior to that of students who learn through direct learning. The type of research is descriptive and quasi-experimental research with a non-equivalent post test-only control group design.The population was 2023/2024 SMPN 2 Lubuk Alung class VIII students. For sampling, researchers utilised simple random sampling. Experimental class wa VIII. 1 and control class was VIII.2 Quizzez and final mathstests were rejecting H0. In class VIII SMPN 2 Lubuk Alung, students who learn with CTL Approach grasp mathematical concepts better than those who learn directly. Keywords – Ability to Understand Mathematical Concepts, CTL Approach, Direct Learning